Rádio escola no ar: a palavra (en)cantada na educação literária antirracista - Ghil, Jamille Gomes (2018)
In this qualitative research, we intend to describe and analyze the practices of literary education carried out during the extension course Escola no Ar (2015 and 2016), with adolescents of Prezideu Amorim Elementary School - located in the Bonfim neighborhood, Vitória - ES. Our objective is to discuss the practices read and say in the light of the humanizing function of literature (CANDIDO, 1997) as a possible contribution to the awareness of the humanity of those who have denied humanity, forming readers critical of racism in Brazil from poems and words not only with the socioeconomic and cultural reality of the students, but also with a view to problematizing the racial condition to which blacks are subjected in the country. To do so, we will consider the notions of racism (d'ADESKY, 2005), read and say (BAJARD, 2014) and literary education (LEAHY-DIOS, 2013).